Examining community participation in process evaluation of humanitarian food security projects in Matobo Zimbabwe - Nyoni, Mbakisi (University of the Witwatersrand, Johannesburg, 2023)
Climate change in Africa has resulted in devastating food insecurity especially among rural households in the semi-arid regions. The purpose of this research was to examine the roles of the local community in the process evaluation of the Fambidzanai Permaculture Centre food security project that is intended to improve food security in Matobo District, Ward 18. One key finding from the study is that community engagement in humanitarian interventions was key to improving community participation in community projects. The study also discovered that major constraints to community participation includes: lack of community inclusion in project design and planning stages, inadequate knowledge of project planning and management and inadequate knowledge of monitoring and evaluation
A research report submitted to the faculty of Management, University of the Witwatersrand, in 50% requirement for the of Master of Management degree (in the field of Public and Development sector Monitoring and Evaluation), Johannesburg, 2023
Keywords: Food security; Process evaluation; UCTD; SDG-2: Zero hunger